Augmented Fluoroscopic Bronchoscopy 2.0: Image Fusion for Endobronchial Roadmapping. Issue 4 (October 2021) - Yang, Shun-Mao; Yu, Kai-Lun; Chen, Lun-Che; Chung, Wen-Yuan; Ko, Huan-Jang; Chen, Chung-Ming
Abstract : Supplemental Digital Content is available in the text.